Pheromones, binding proteins, and olfactory systems in the pig (Sus scrofa): An updated review - Sankarganesh, Devaraj; Kirkwood, Roy N.; Nagnan-Le Meillour, Patricia; Angayarkanni, Jayaraman; Achiraman, Shanmugam; Archunan, Govindaraju (Frontiers in Veterinary Science, 2022)
Pigs utilize multimodal communication for reproductive and other behaviors, and chemical communication is one of the key components. The success of reproduction relies on chemical communication favored by the steroid pheromones from boar saliva. These steroids were proven to be involved in advancing puberty in gilts (the boar effect) and in promoting estrus behaviors in gilts/sows, thereby helping to detect estrus and facilitating the timing of artificial insemination. The steroid pheromones bound with carrier proteins are evidenced in the mandibular (submandibular) salivary secretions of the boar. These salivary steroids bind with carrier proteins in the nasal mucus and vomeronasal organ (VNO) of the sows, eventually triggering a cascade of activities at the olfactory and endocrine levels. Besides steroid pheromones, pig appeasing pheromones (from mammary skin secretions of sows) have also been demonstrated to bind with carrier proteins in the nasal mucus and VNO of the piglets. Thus far, four different proteins have been identified and confirmed in the nasal mucus and VNO of pigs, including odorant binding proteins (OBPs), salivary lipocalin (SAL), pheromaxein, and Von Ebner’s Gland Protein (VEGP). The critical roles of the chemosensory systems, main olfactory systems and VNO, have been comprehensively reported for pigs. This review summarizes the current knowledge on pheromones, their receptor proteins, and the olfactory systems of porcine species.